An Introduction to the Cypriot Literature for Children, with an Emphasis on Poetry for Children - Papantonakis, George (Études helléniques / Hellenic Studies, 2007)
In Cyprus, children’s literature reached a more mature stage during the last decades. A great many poems and stories for children are published, and some have been commercial successes in Greece. This article covers the main features, technical processes and themes of children’s literature, with an emphasis on poems.